The influence of temperament types and introversion/extraversion on a choice of coping stratigies - Tetyna Andrusyschyna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article devoted to study the impact of the temperament type and introversion / extraversion on a choice of coping strategies. The following tests are used: Eysenck Personality Inventory (EPI, option A) to identify extraversion/introversion and temperament type, also personality questionnaire "Winning Ways behavior" Lazarus to define the major copings trategies. The sample consisted of 64 respondents, study results was processed by using a statistical computer program SPSS.